DRY MATTER, CRUDE PROTEIN, AMMONIACAL NITROGEN AND pH OF THREE PEARL MILLET GENOTYPES SILAGES [Pennisetum glaucum (L). R. BR.] IN DIFFERENT FERMENTATION PERIODS - ROBERTO GUIMARÃES JÚNIOR (Revista Brasileira de Milho e Sorgo, 2005)
The dry matter (DM), crude protein (CP), ammoniacal nitrogen (N-NH3) and pH values were determined in three pearl millet genotypes silage, after 1, 3, 5, 7, 14, 28 and 56 days ensiling in PVC laboratory silos. Dry matter contents of silage ranged from 23.12 to 24.49%; CP mean levels were 10.95% for green forages and 10.40% for silage in the 56th day. In the last evaluation period the N-NH3 and pH mean values were 8.75% and 3.62, respectively. DM and CP contents remained constant (P>0.05) and the N-NH3 values significantly increased, not tending to stability, along the whole fermentation process. However, pH values stabilized after 14 days ensiling.